2008
DOI: 10.1111/j.1462-2920.2008.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

The small genome of an abundant coastal ocean methylotroph

Abstract: OM43 is a clade of uncultured beta-proteobacteria that is commonly found in environmental nucleic acid sequences from productive coastal ocean ecosystems, and some freshwater environments, but is rarely detected in ocean gyres. Ecological studies associate OM43 with phytoplankton blooms, and evolutionary relationships indicate that they might be methylotrophs. Here we report on the genome sequence and metabolic properties of the first axenic isolate of the OM43 clade, strain HTCC2181, which was obtained using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
224
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(242 citation statements)
references
References 58 publications
13
224
0
1
Order By: Relevance
“…The large subunit of the OM43 clade methanol dehydrogenase (MDH) (XoxF aka MxaF) was the best match to 2.3% of all the spectra identified, lending further support to recent findings that implicate methanol and other one carbon compounds as important substrates for bacterioplankton in coastal ecosystems (Giovannoni et al, 2008). A total of 168 spectra matching 33 eCDSs were closest matches to the OM43 clade MDH (Figure 4).…”
Section: Frequently Detected Proteinssupporting
confidence: 59%
See 2 more Smart Citations
“…The large subunit of the OM43 clade methanol dehydrogenase (MDH) (XoxF aka MxaF) was the best match to 2.3% of all the spectra identified, lending further support to recent findings that implicate methanol and other one carbon compounds as important substrates for bacterioplankton in coastal ecosystems (Giovannoni et al, 2008). A total of 168 spectra matching 33 eCDSs were closest matches to the OM43 clade MDH (Figure 4).…”
Section: Frequently Detected Proteinssupporting
confidence: 59%
“…The betaproteobacterial OM43 clade is commonly found at low levels in coastal ecosystems and has been observed to increase in abundance to B2% of bacterial cells during phytoplankton blooms (Morris et al, 2006). Phylogenetic and genome analysis of the OM43 isolate HTCC2181 placed this organism among type I methylotrophs that can use methylated compounds as a sole carbon and energy source (Giovannoni et al, 2008). It was also shown that cell growth yield was proportional to the amount of methanol or formaldehyde added to sterile seawater media.…”
Section: Frequently Detected Proteinsmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with other coastal studies (Sowell et al, 2011;Williams et al, 2012), we detected the expression of methanol dehydrogenase large subunit proteins derived from the Beta-proteobacteria OM43 clade (Table 3). Methanol dehydrogenase was detected in all samples and exhibited highest similarity to homologs from two methylotrophic strains (HTCC2181 and KB13; Supplementary Table S8; Giovannoni et al, 2008). On the basis of previous genome analysis, OM43 bacteria use the RuMP pathway for the assimilation of carbon from C1 compounds (Giovannoni et al, 2008).…”
Section: One Carbon Metabolismmentioning
confidence: 99%
“…Methanol dehydrogenase was detected in all samples and exhibited highest similarity to homologs from two methylotrophic strains (HTCC2181 and KB13; Supplementary Table S8; Giovannoni et al, 2008). On the basis of previous genome analysis, OM43 bacteria use the RuMP pathway for the assimilation of carbon from C1 compounds (Giovannoni et al, 2008). Here, we also identified the expression of a key enzyme of the RuMP pathway, namely hexulose-6-phosphate synthase, in all samples (Table 3, Supplementary Table S8), suggesting OM43 may be assimilating carbon derived from methanol.…”
Section: One Carbon Metabolismmentioning
confidence: 99%